Urban foodscape transformation and tourist culinary preferences: evidence from Jakarta’s Blok M - Suci Sandi Wachyuni; Kadek Wiweka; Asep Parantika (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2026)
This study examines how the rapid expansion of the urban culinary industry shapes tourists’ preferences for local and foreign cuisine within the context of urban gastronomic destinations. the research aims to analyse tourist behaviour in selecting culinary offerings in the Blok M area by applying the Theory of Planned Behavior (TPB) framework and identifying key determinants influencing such preferences. A descriptive quantitative approach was employed using accidental sampling of 111 domestic tourists visiting the area between September and November 2025. Data were collected through a structured questionnaire using a five-point Likert scale and analysed using frequency distribution, mean score analysis, and cross-tabulation techniques to examine relationships between demographic characteristics and culinary preferences. The findings reveal that the culinary landscape in Blok M is predominantly characterised by foreign cuisine (68%), with the majority of respondents (59.5%) expressing a preference for international food options, particularly among younger tourists aged 17–35 years. In contrast, tourists aged above 36 years demonstrate a stronger preference for local cuisine. Based on TPB analysis, perceived behavioural control (mean = 4.31) emerges as the most influential construct in shaping purchase intention, followed by subjective norms (4.19) and attitudes (4.11).